Case Report: Early presentation of hereditary angioedema symptoms in a 2-year-old boy - Staikuniene-Kozonis, Jurate; Staikunaite, Juste; Gasiuniene, Edita; Sematonyte, Justina (Frontiers in Pediatrics, 2024)
Hereditary angioedema (HAE) is a rare autosomal dominant disease that is caused by deficiency (type I) or dysfunction (type II) of the C1 inhibitor (C1-INH) due to a mutation in the SERPING1 gene, which codes for C1-INH. HAE with quantitatively and qualitatively normal C1-INH (type III) is often due to a mutation in the F12 gene and no mutations in the SERPING1 gene and is a group of very rare diseases . C1 esterase inhibitor (C1-INH) is a major regulator of critical enzymes that are implicated in the cascades of bradykinin generation, which increases the vascular permeability and allows the flow of fluids into the extracellular space and results in angioedema. HAE clinically manifests with intermittent attacks of swelling of the subcutaneous tissue or submucosal layers of the respiratory and gastrointestinal tract. Young children are typically asymptomatic, those affected by HAE usually present with symptoms in their early 20s. This article describes the case of very early onset of hereditary angioedema caused by C1 inhibitor (C1-INH) deficiency in a 2-year-old boy who experienced recurrent episodes of hand and abdominal angioedema not associated with urticaria or pruritus. His father suffered from severe HAE due to de novo mutation of SERPING 1gene. The same mutation of SERPING1 gene was detected to his son at the age of 9 months prior to angioedema symptoms started during the genetic family counseling . This paper advances the understanding of HAE and highlights the importance of genetic counseling of families with HAE in order to avoid late or inaccurate diagnosis and to initiate the treatment on time.